Understanding consumer behaviour in The Vodka market - Mendes, Ana Rita Gonçalves Santinho (2023)
There has been an increasing growth of the distilled beverages consumption in Portugal, mostly among young generations. Recent studies proved young consumers drink almost four times more vodka than the average Portuguese consumer. The present research focuses on understanding consumer behaviour in the vodka market through interviews with market experts and vodka consumers and conducting structured surveys. Applying market research techniques such as maps and conjoint analysis, it was possible to understand how consumers perceive some existing brands – Eristoff, Smirnoff, Misss, Grey Goose, Cirôc and Absolut -, their preferences regarding product features and also to identify the main consumer decision making styles. It was verified that quality is associated with price, being the two most important attributes in the consumer decision-making of vodka and that although Portuguese vodka consumers are essentially price driven, they have minimum standards for quality. In addition, Cirôc and Grey Goose were perceived as the highest quality and sophisticated brands, while Eristoff and Absolut are more associated to excitement and enthusiasm.